Application of PSO technique for optimal location of FACTS devices - Suhairah, Razali (2009)
The application of Particle Swarm Optimization (PSO) technique to find optimal location of Flexible AC Transmission System (FACTS) devices to achieve maximum system loadability. While finding the optimal location, thermal limit for the lines and voltage limit for the buses are taken as constraints. Two types of FACTS devices, Unified Power Flow Controller (UPFC) and thyristor Controlled Series Compensator (TCSC) are considered. The optimizations are performed on three parameters namely the location of FACTS devices, their setting and their type. Simulations are performed on IEEE 30-bus system for optimal location of FACTS devices and the results obtained are encouraging and will be useful in electrical restructuring.